Entrepreneur Voices on Emotional Intelligence. - Small, Jonathan; Howes, Lewis (Entrepreneur Voices., 2018)
Entrepreneur Voices on Emotional Intelligence shares the battle-tested strategies and tactics for improving and maintaining your own emotional intelligence as you learn to perceive emotions to better handle the behaviors, personalities, and body language of those around you.